THE POST – ASEAN’S HAZE-FREE ROADMAP 2020 AND IMPLEMENTATION OF PRECAUTIONARY PRINCIPLE IN INDONESIA’S ENVIRONMENTAL DIPLOMACY: RIAU’S PERSPECTIVE - Afajri Afajri; Herry Wahyudi; Azhari Setiawan (Faculty of Social and Political Sciences University of Bangka Belitung, 2021)
The ASEAN’s haze-free roadmap 2020 had the objective to eliminate the regional transboundary haze pollution. However, the 2019 haze recurrence which mostly originated from Indonesia’s land and forest had caused a diplomatic uproar between Indonesian and Malaysian top government officials. In addition, land and forest fires continued to occur in Indonesia over the last 5 years, albeit with a much lower severity compared to 2015, and did not gain global media attention as the haze rarely crossed out of Indonesia’s jurisdiction. This research applies qualitative research method where the data collection is based on semi-structured interviews involving multi-stakeholders in Riau Province. Additional data are also collected from various journals, books, and news from media archival. The finding of this research discloses that several new policies and programs have been created and introduced since the last 5 years provided an early positive start, however, further implementation on the ground has been weak and complicated. Furthermore, previous, current, and future unchanged negligence behavior of government elites and public in Riau towards the land and forest fires has left the post – ASEAN’s haze-free roadmap 2020 with an equal or more amount of homework in the future. Thus, Indonesia needs to pay more attention and work in a sustainable manner on this issue, especially at the local level such as in Riau province and other land and forest fire-prone provinces in order to strengthen Indonesia's environmental diplomacy bargaining position in the globe and enlighten the current gloomy image in the future.